Implicit bias towards people with disability in Australia: relationship with personal values - Christine R. Antonopoulos; Nicole Sugden; Anthony Saliba (Australian Journal of Psychology, 2025)
Objective This study investigated implicit bias towards people with disability and the relationship between implicit bias and personal values.Method A convenience sample of 146 people living in Australia completed an online survey that included the Portrait Values Questionnaire – Revised (PVQ-RR), experience with disability questions, and two Implicit Association Tests (IAT) that measured stereotypes of incompetency and coldness towards people with disability.Results There was a moderate IAT effect, with 80.1% of participants implicitly stereotyping people with disability as incompetent and 74.1% implicitly stereotyping people with disability as cold. Personal values of universalism-concern and universalism-tolerance were significantly positively correlated, and security-society was significantly negatively corelated with the Competence IAT. Universalism-concern and Self-transcendence were significantly positively correlated with the Warmth IAT. Higher scores on universalism-concern and if a person had a disability predicted lower implicit stereotyping of people with disability as incompetent. Higher scores on universalism-concern and Self-transcendence predicted lower stereotyping of people with disability as cold.Conclusion People in Australia have similar moderate negative implicit biases towards people with disability as reported in other countries. Personal values identified could be targeted in reflective practice interventions with employment and healthcare professionals to reduce the effects of implicit bias towards people with disability.